Travel Behaviors and Needs of Senior Visitors for Tourism in Khao Yai National Park - Puangchuen, Kanjanawadee; Phumsathan, Sangsan (Journal of Thai Hospitality and Tourism, 2020)
This study was designed to find out tourism behaviors and the needs of facilities and services for senior visitor. The result was used as the guideline for the senior tourism management in Khao Yai National Park. A set of 642 questionnaires was used to collect data from Thai tourists aged 60 years and over, who travelling to Khao Yai National Park by convenience sampling, from August 2016 - May 2017. Descriptive analysis and factor analysis were used for data analysis. The result presented that most of the senior visitors were female, 60 - 69 years old, and came from the central of Thailand. Besides, a majority of respondents have hypertension problems, however, it was not a barrier to travel. Most tourists travelled for one day trip with their families by their own car. Travel motivation was the purity of the environment. Popular activities for senior tourists were passive activities such as scenic viewing, leisure, and photographing. The needs for facilities and services were classified into seven groups. The result also showed that senior visitors’ needs for facilities and services were in relation to tourist accommodation with the highest significance, followed by travel activities, and special services for seniors. From the result, Khao Yai National Park should promote and develop family tourism activities, especially passive activities. Furthermore, for senior tourism development, the priority is to improve facilities and services related to tourist accommodation by using the concept of universal design, especially basic facilities, and safety.